2020
DOI: 10.1093/mnras/staa1820
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR observations of four nearby X-ray faint AGNs: low luminosity or heavy obscuration?

Abstract: We present NuSTAR observations of four active galactic nuclei (AGN) located within 15 Mpc. These AGN, namely ESO 121-G6, NGC 660, NGC 3486 and NGC 5195, have observed X-ray luminosities of L2-10 keV, obs ≲ 1039 erg s−1, classifying them as low luminosity AGN (LLAGN). We perform broadband X-ray spectral analysis for the AGN by combining our NuSTAR data with Chandra or XMM-Newton observations to directly measure their column densities (NH) and infer their intrinsic power. We complement our X-ray data with archiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Thus, the baseline model used in this work will lead to robust results that can be easily compared with previous works (e.g. Annuar et al 2015Annuar et al , 2017Annuar et al , 2020Kawamuro et al 2016 ).…”
Section: Baseline Modelsmentioning
confidence: 86%
“…Thus, the baseline model used in this work will lead to robust results that can be easily compared with previous works (e.g. Annuar et al 2015Annuar et al , 2017Annuar et al , 2020Kawamuro et al 2016 ).…”
Section: Baseline Modelsmentioning
confidence: 86%
“…Interestingly, this situation is reminiscent of NGC 3486-as one example-in that a high-excitation line attributed to AGN activity was reported (O VI in NGC 3486 and Ne V in NGC 4178; Satyapal et al 2009;Annuar et al 2020), and an AGN was reported based on soft X-ray emission from XMM-Newton (L 2-10keV = 1.1 × 10 39 erg s −1 in NGC 3486; Cappi et al 2006) or Chandra (L 2-10keV = 7.9 × 10 38 erg s −1 in NGC 4178; Secrest et al 2012) but was not detected in the NuSTAR imaging (Annuar et al 2020, and this work). The major difference in this comparison is that NGC 3486 is detected as a Type II AGN in the optical, whereas NGC 4178 presents as an H II star-forming region.…”
Section: Ngc 4178mentioning
confidence: 93%
“…With the exception with the outer most ring, NGC 3486 has one of the most obvious examples of 𝑡 𝑦𝑆 𝑃 decreasing and 𝑓 𝑏𝑢𝑟 𝑠𝑡 increasing with galactocentric radius. The central region is host to a possible Type 2 Seyfert (Ho et al 1997;Annuar et al 2020). The outermost region, although slightly bluer than the intermediate regions, has a similar 𝑡 𝑦𝑆 𝑃 as the intermediate regions.…”
Section: A3 Ngc 3486mentioning
confidence: 99%